Preclinical testing of theranostic graphene-based magnetic nanocarriers in 2D and 3D hepatocellular carcinoma models - Costa, Vánia Catarina da Silva (2021)
Dissertação de mestrado em Biomedical Engineering Biomaterials, Rehabilitation e Biomechanics Branch